Improving Passenger Satisfaction through Six Sigma: An Analysis of BRT Trans Jateng Corridor 7 - Primasanti, Yunita; Wahyu, Indah; Nugrahadi, Bekti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Bus Rapid Transit (BRT) systems play a crucial role in providing efficient and sustainable urban mobility, yet service quality often faces challenges that lead to passenger dissatisfaction. This study focuses on BRT Trans Jateng Corridor 7, which has received a considerable number of complaints regarding service reliability, comfort, and punctuality. The main objective of this research is to improve passenger satisfaction by applying the Six Sigma methodology to identify, analyze, and reduce the root causes of service-related complaints. Using the DMAIC (Define, Measure, Analyze, Improve, Control) framework, data were collected through complaint reports, passenger surveys, and operational performance indicators. Statistical analysis and cause-effect diagrams were employed to pinpoint critical factors influencing complaints, including bus frequency, driver performance, ticketing efficiency, and infrastructure support. The findings indicate that the application of Six Sigma significantly reduced recurring complaints, particularly in the areas of schedule adherence and service responsiveness, leading to measurable improvements in overall passenger satisfaction. The synthesis of results demonstrates that structured quality management approaches such as Six Sigma can effectively enhance public transportation service quality by providing systematic solutions to operational problems. In conclusion, this research highlights the practical benefits of Six Sigma in improving service performance and reducing passenger complaints, offering valuable insights for policymakers and transportation operators seeking to strengthen the quality and sustainability of public transit systems.